H3K27me3 modulates trained immunity of monocytes in HDM-allergic diseases - Lingli Han; Lingli Han; Lin Li; Liangjiao Yao; Huaqin Bu; Yajie Tian; Qifan Li; Ke Zhu; Ke Zhu; Haili Yao; Xiaochuan Wang; Maoxiang Qian; et al. (Frontiers in Immunology)
BackgroundMonocytes have been confirmed to increase in persistently food-allergic children. A phenomenon of innate immune memory, called trained immunity, has also been observed in monocytes from allergic children. However, the underlying mechanism remains poorly understood.MethodsWe enrolled a cohort of HDM-allergic children alongside age-matched healthy controls and established an HDM-sensitized allergic mouse model. Flow cytometric analyses were conducted to quantify monocyte frequencies in clinical cohorts and experimental animals. We performed integrated transcriptomic profiling via RNA-seq combined with chromatin occupancy analysis using CUT&Tag technology in parallel human and murine samples to elucidate the molecular mechanisms.ResultsIn our study, we demonstrated a reduced H3K27me3 methylation level accompanied by an increased proportion and a proinflammatory transcriptional memory in monocytes from house dust mite (HDM)-allergic human subjects. The same transcriptional and epigenetic phenotype was also confirmed in HDM-sensitized mice. Finally, the administration of GSK-J4, which upregulates H3K27me3 level in murine monocytes, attenuated the inflammatory response in vitro and in vivo.ConclusionsOur study confirms that H3K27me3 methylation modulates the trained immunity in monocytes and regulates HDM-allergic diseases through an inflammatory-dependent mechanism.